Posterior Column Triangle Fluoroscopic View for Posterior Column Screw Placement in Acetabular Surgery: A Novel Single Fluoroscopic View Technique - Sikarinkul, Eakachit; Puangnam, Prakatchai; Mayurasakaorn, Chatchanin; Phiphobmongkol, Vajara; Bavonratanavech, Suthorn (The Bangkok Medical Journal, 2025)
OBJECTIVES: Posterior column screw placement is essential for achieving fracture stability in acetabular fractures involving the posterior column. The conventional technique requires multiple intraoperative fluoroscopic views, increasing both radiation exposure and operative time. This experimental study aimed to assess the efficacy and safety of a single intraoperative fluoroscopic view, guided by the “posterior column triangle” concept, for posterior column screw placement in a pelvic bone model, compared to the conventional two-view technique. MATERIALS AND METHODS: The study was conducted using pelvic bone models and involved five surgeons with varying levels of experience in pelvic surgery, including pelvic and acetabular specialists and orthopedic trauma fellows. Each surgeon performed posterior column screw insertions using both the conventional two-view fluoroscopic technique (anteroposterior and iliac oblique views) and a novel single-view technique guided by the “posterior column triangle” concept. In this approach, the defined triangle served as the safe corridor for the entry and ending points of the screw trajectory. The optimal fluoroscopic angle for the single-view, termed the “posterior column triangle view,” was determined to be 10 degrees obturator tilt and 25 degrees inlet tilt. Data on screw insertion safety and radiation exposure were collected and analyzed. RESULTS: The novel single-view fluoroscopic technique consistently enabled accurate K-wire placement within the safe corridor of the posterior column, with no cortical breaches observed in any of the tested bone models. Additionally, it was associated with significantly reduced radiation exposure compared to the conventional two-view method. These findings suggest that the single-view approach may serve as a viable alternative in clinical practice, particularly for managing high posterior column fractures. CONCLUSION: The posterior column triangle-view technique offers a safe alternative for K-wire insertion in posterior column screw fixation while reducing radiation exposure. Implementation of this technique should be considered in high posterior column fracture line. Further larger-scale studies with different pelvic bone samples are warranted.